Telepsychiatry for Mental Health Service Delivery to Children and Adolescents - Kommu, John Vijay Sagar (Indian J Psychol Med, 2020)
Children constitute 40% of India’s population. Large number of children with psychiatric disorders and neurodevelopmental conditions are unable to access mental health services due to factors such as unavailability of these services in smaller urban and rural centres and lack of training for primary care providers. Given the relatively easy access to video conferencing technology, feasibility and acceptability of Telepsychiatry, there is an urgent need to invest resources and strengthen the use of Telepsychiatry for child and adolescent mental health training and serviced delivery . This viewpoint article discusses the need,scope,experiences and challenges related to use of Telepsychiatry in the area of child mental health.